Animal Models of Anxiety and Depression: Incorporating the Underlying Mechanisms of Sex Differences in Macroglia Biology - Wegener, Amy J.; Neigh, Gretchen N. (Frontiers in Behavioral Neuroscience, 2021)
Animal models have been utilized to explore the mechanisms by which mood disorders develop. Ethologically based stress paradigms are used to induce behavioral responses consistent with those observed in humans suffering from anxiety and depression. While mood disorders are more often diagnosed in women, animal studies are more likely to be carried out in male rodents. However, understanding the mechanisms behind anxiety- and depressive-like behaviors in both sexes is necessary to increase predictive and construct validity of the models and identify therapeutic targets. To understand sex differences following stress, we must consider how all cell types within the central nervous system are influenced by the neuroendocrine system. This review article discusses the effects of stress and sex steroids on the macroglia: astrocytes and oligodendrocytes. Glia are involved in shaping the synapse through the regulation of neurotransmitter levels and energy resources, making them essential contributors to neural dynamics following stress. As the role of glia in neuromodulation has become more apparent, studies exploring the mechanisms by which glia are altered by stress and steroids will provide insight into sex differences in animal models. These insights will facilitate optimization of animal models of psychiatric disorders and development of future therapeutic targets.